Influence of silver additions on the aging characteristics of the Cu-10.4at.%Al alloy - Adorno, A. T. [UNESP]; Guerreiro, M. R. [UNESP]; Benedetti, A. V. [UNESP] (My University, 1998)
The influence of additions of 1.3, 2.5, 3.8, 5.1, and 6.3 at.% Ag on the aging behavior of the Cu-10.4at.%Al alloy was studied using microhardness measurements, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) analysis. The results indicated that with silver additions it is possible to obtain a response to age hardening, and that for large aging times there is a decrease in the alloy hardness, with a process that leads to Ag and Al segregation. © 1998 Elsevier Science S.A.
Keywords: Aging; Copper-based alloys; Microhardness; Silver additions; Ternary systems; Age hardening; Composition effects; Hardness testing; Mechanical variables measurement; Scanning electron microscopy; Segregation (metallography); Silver; X ray analysis; Energy dispersive X ray (EDX) analysis; Copper alloys